Application of Sound Wave Theory as an Alternative to Teach Sound Detection for Students with Hearing Impairments using Cochlear Implants - Muspita, Rila; Hufad, Achmad; Syihabuddin; Nandiyanto, sep Bayu Dani; Manullang, Tryastuti I B; Efrina, Elsa; Yulistian, Lilis (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to improve students with hearing impairments using cochlear implants’ knowledge of the application of sound wave theory and sound detection and also to identify the respiration ability of the student. This study used a mixed method approach of 4 students with hearing impairment using cochlear implants in Bandung Hearing Care. The results showed that the students understand the source of sound, the students can detect sound and do respiration by blowing the measuring cylinder to produce sound, the students can distinguish the sound produced from an empty measuring cylinder, measuring cylinder containing 150 mL of colloid and containing 250 mL of colloid, and the students were interested with the activities because it was their first experience. These happened due to the use of implants for more than 2 years. Although students can speak, they find difficulties hearing some words when the distance is more than 3 meters. The students are quite cooperative and have understood simple instructions.